Prevention and management of cytomegalovirus infection and disease in kidney transplant: A consensus statement of the Transplantation Society of Taiwan - Mu-Chi Chung; Cheng-Hsu Chen; Shen-Shin Chang; Chih-Yuan Lee; Ya-Chung Tian; Mei-Yi Wu; Hsu-Han Wang; Chia-Cheng Yu; Teng-Wei Chen; Chien-Chang Kao; Chih-Yang Hsu; Yang-Jen Chiang; et al. (Journal of the Formosan Medical Association)
Kidney transplant recipients have an increased risk of cytomegalovirus (CMV) infection and disease. A strategy for mitigating the risk of CMV infection in kidney transplant recipients has not yet been established in Taiwan. The Transplantation Society of Taiwan aimed to develop a consensus by expert opinion on the prevention and management of CMV infection. Based on the results of Consensus Conference, we suggested low-dose valganciclovir prophylaxis (450 mg once daily) for kidney transplant recipients. The prophylaxis duration was ≥6 months for high-risk (D+/R-) patients and 3 months for moderate-risk (R+) patients. Even for low-risk (D-/R-) patients, prophylaxis for at least 3 months is recommended because of the high seroprevalence of CMV in Taiwan. CMV prophylaxis was suggested after anti-thymocyte globulin treatment but not after methylprednisolone pulse therapy. Routine surveillance after prophylaxis, secondary prophylaxis after CMV disease treatment, and mTOR inhibitors for primary CMV prophylaxis were not recommended. Letermovir and marabavir are emerging CMV agents used for prophylaxis and refractory CMV disease. CMV immunoglobulins have been used to treat refractory CMV disease in Taiwan. We hope this consensus will help professionals manage patients with CMV in Taiwan to improve the quality of care.